Antecedentes da lealdade e moderação intergeracional de clientes: um estudo com um provedor de serviços bancários no Brasil - Wink, Daniela Regina Lassen (Universidade do Vale do Rio dos Sinos, 2021)
Maintaining customer loyalty is a complex challenge, especially considering customers with diverse experiences, motivations and expectations in a traditional sector such as banking. In a context of new entrants in this market, understanding the antecedents and moderators of loyalty among different generations of customers can help banks retain their customers more and promote actions to win over, especially the younger ones, as they tend to be less loyal. This study analyzed the value-in-use, trust and satisfaction constructs as antecedents of loyalty, and also the different generations as a moderating variable in the relationship between these antecedents and customer loyalty, considering the baby boomer, X and Y generations, in one of the largest banks in Brazil, referred to in this study as Banco X. A survey-type survey was conducted with 314 respondents. The results of this study indicate that loyalty is positively and significantly influenced by value-in-use and satisfaction. Interestingly, according to this research loyalty is not positively and significantly influenced by trust. Another finding of this research is the confirmation of the moderating effect of the baby boomers and X generations, in the relationship between customer satisfaction and loyalty, that is, for these two generations, the more satisfied, the more loyal the customer is.
Keywords: Lealdade; Satisfação; Confiança; Valor de uso; Gerações; Loyalty; Satisfaction; Trust; Value-in-use; Generations; ACCNPQ::Ciências Sociais Aplicadas::Administração